Acrylic acid dispersion suitable for metal anti-corrosion paint as well as preparation and application of acrylic acid dispersion
By preparing lysine-grafted modified polylactic acid intercalated bentonite, the problems of uneven filler dispersion and insufficient bonding in the existing technology were solved, thereby improving the corrosion resistance and physical strength of metal anti-corrosion coatings.
Patent Information
- Application Number
- CN202511298661.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-11
- Publication Date
- 2025-12-02
AI Technical Summary
Existing acrylic dispersions suffer from uneven filler dispersion and insufficient bonding with bentonite, resulting in inadequate corrosion resistance. Furthermore, traditional additive fillers are prone to settling and uneven dispersion, affecting the mechanical and corrosion resistance of the coating.
By preparing lysine-grafted modified polylactic acid and intercalating it into sodium-based bentonite, the polar groups of lysine are used to expand the spacing between bentonite layers, forming uniformly dispersed nanosheets, which enhances the binding ability with resin. The addition of intercalated bentonite composite filler improves the corrosion resistance.
This method achieves uniform dispersion of nanosheets in a polylactic acid matrix, enhancing the physical strength and corrosion resistance of the coating, and improving its weather resistance and rust prevention.
Smart Images

Figure CN121045900A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of acrylic coating technology, specifically to an acrylic dispersion suitable for metal anti-corrosion coatings, and its preparation and application. Background Technology
[0002] Acrylic dispersions are stable waterborne resin systems formed by dispersing acrylic monomers in water through emulsion polymerization or solution polymerization. They include a resin matrix, a water dispersion medium, and functional additives. Depending on the application, functional additives such as anti-corrosion pigments, nanofillers, and curing agents can be added to form a composite system. The addition of anti-corrosion fillers can bring anti-corrosion properties to coatings prepared from acrylic dispersions. Metal structures are highly susceptible to corrosion from water, oxygen, chloride ions, and other corrosive media in marine, chemical, and humid environments. Coatings prepared from waterborne acrylic dispersions have become the mainstream film-forming material for metal anti-corrosion primers due to their good film-forming properties, strong adhesion, and anti-corrosion performance.
[0003] In existing technologies, bentonite is typically added as a filler in acrylic dispersions. Sodium-based bentonite is composed of stacked aluminosilicate sheets, possessing a large specific surface area, high aspect ratio, and excellent barrier properties. However, strong van der Waals forces exist between the sheets, making it difficult to peel into single layers using conventional mechanical dispersion. Furthermore, to further improve corrosion resistance, zinc powder or flaky mica is added as a rust-inhibiting filler. However, these additive fillers are prone to sedimentation and uneven dispersion, and their bonding ability with the bentonite and resin interface is weak, leading to powdering of the coating after long-term weathering. Intercalation bonding of the rust-inhibiting filler with bentonite could potentially solve these problems. Therefore, this invention provides an acrylic dispersion suitable for metal anti-corrosion coatings, its preparation, and its application. This approach overcomes the shortcomings of traditional acrylic dispersions, such as uneven filler dispersion and insufficient bonding with bentonite, resulting in inadequate mechanical and anti-corrosion properties, thus addressing the problems existing in the prior art. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide an acrylic dispersion suitable for metal anti-corrosion coatings, as well as its preparation and application.
[0005] A method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings includes the following steps: S1: Preparation of lysine-grafted modified polylactic acid Polylactic acid was dissolved in anhydrous dimethyl sulfoxide, and EDC and N-hydroxysuccinimide were added. The mixture was reacted to obtain a polylactic acid mixture. Lysine was added to PBS buffer and stirred to obtain a lysine buffer. The polylactic acid mixture was added to the lysine buffer and stirred. The reaction solution was then poured into ice-cold ether to precipitate. The solid was collected by filtration, dialyzed with pure water, and freeze-dried to obtain lysine-grafted modified polylactic acid. S2: Preparation of intercalated bentonite composite filler Sodium-based bentonite was dispersed in deionized water and stirred. Octadecyltrimethylammonium chloride was then added to react and obtain treated bentonite. Lysine-grafted modified polylactic acid was dissolved in a chloroform / toluene mixed solvent and stirred to obtain a suspension. The treated bentonite was added to a toluene solution and ultrasonically treated to obtain a bentonite dispersion. The bentonite dispersion was added dropwise to the suspension, and the mixture was sheared at high speed, stirred, and dried to obtain an intercalated premix. The intercalated premix was pulverized and extruded to granulate to obtain an intercalated bentonite composite filler. S3: Preparation of acrylic dispersions suitable for metal anti-corrosion coatings Methyl methacrylate, butyl acrylate, acrylic acid, and emulsifier were added to deionized water and sheared and emulsified. Ammonium persulfate aqueous solution was added, and the reaction was carried out under heat. Intercalated bentonite composite filler was added, and the mixture was stirred. EDC was added, and the reaction was carried out to obtain an acrylic dispersion suitable for metal anti-corrosion coatings.
[0006] Further, step S1 prepares lysine-grafted modified polylactic acid, including the following steps: S1.1: Dissolve 5-10 parts by weight of polylactic acid in 200-202 parts by weight of anhydrous dimethyl sulfoxide, stir at 65-70°C under nitrogen protection until completely dissolved, then cool to 25-30°C and adjust the pH to 5.5-6, add 3-5 parts by weight of EDC and 4-6 parts by weight of N-hydroxysuccinimide, react for 4-4.5 h to obtain a polylactic acid mixture; S1.2: Add 4-8 parts by weight of lysine to 100-105 parts by weight of PBS buffer and stir for 5-10 min to obtain lysine buffer. Add polylactic acid mixture to lysine buffer and stir at 25-30℃ for 24-25 h under nitrogen atmosphere. Then pour the reaction solution into ice-cold ether to precipitate, filter to collect solid, wash three times with anhydrous ethanol and deionized water respectively, dialyze with pure water for 48-50 h, and freeze-dry to obtain lysine-grafted modified polylactic acid.
[0007] Further, step S2, preparing the intercalated bentonite composite filler, includes the following steps: S2.1: Disperse 5-8 parts by weight of sodium-based bentonite in 500-510 parts by weight of deionized water, stir at 80-85℃ and 3000-3100 r / min for 10-15 min, then add 6-7 parts by weight of octadecyltrimethylammonium chloride, react for 4-4.5 h, centrifuge and wash, dry at 60-65℃ for 24-25 h, pulverize and pass through a 300 mesh sieve to obtain treated bentonite; S2.2: Lysine-grafted modified polylactic acid was dissolved in a chloroform / toluene mixed solvent at a material-to-liquid ratio of 1g:(20-22)mL and stirred at 60-65℃ to obtain a suspension; S2.3: Add the treated bentonite to toluene solution at a material-to-liquid ratio of 1g:(20-22)mL, and sonicate for 30-35min to obtain a bentonite dispersion; S2.4: Add the bentonite dispersion dropwise to the suspension, and simultaneously shear at 5000-5100 r / min for 30-35 min, heat to 70-75℃, and stir for 6-6.5 h to react. Then, remove 75-80% of the solvent by rotary evaporation. Pour the remaining slurry into a polytetrafluoroethylene mold and vacuum dry at 60-65℃ for 48-50 h to obtain the intercalated premix. After crushing the intercalated premix, granulate it by extrusion through a twin-screw extruder to obtain the intercalated bentonite composite filler.
[0008] Further, step S3, preparing an acrylic dispersion suitable for metal anti-corrosion coatings, includes the following steps: Add 40-45 parts by weight of methyl methacrylate, 30-35 parts by weight of butyl acrylate, 5-8 parts by weight of acrylic acid, and 2-2.5 parts by weight of emulsifier to 250-260 parts by weight of deionized water, and shear emulsify at 2000-2100 r / min for 15-20 min. Under nitrogen protection, heat to 80-85℃, add 0.4-0.5 parts by weight of ammonium persulfate aqueous solution, keep the reaction at this temperature for 1-1.5 h, cool to 40-45℃, add 10-15 parts by weight of intercalated bentonite composite filler, stir at 800-850 r / min for 10-15 min, add 0.3-0.5% by weight of EDC (ethyl acetate) of the total system mass, and react at 40-45℃ for 2-2.5 h to obtain an acrylic dispersion suitable for metal anti-corrosion coatings.
[0009] Furthermore, the pH of the PBS buffer is 8-8.5.
[0010] Furthermore, the chloroform / toluene mixed solvent is prepared by mixing chloroform and toluene in a volume ratio of (4-5):1.
[0011] Furthermore, the power of the ultrasonic treatment is 600W.
[0012] Furthermore, the emulsifier is COPS-1 emulsifier.
[0013] An acrylic dispersion suitable for metal anti-corrosion coatings is prepared by the above-described method for preparing acrylic dispersions suitable for metal anti-corrosion coatings.
[0014] An application of an acrylic dispersion suitable for metal anti-corrosion coatings, which is used in the preparation of metal anti-corrosion coatings.
[0015] Compared with the prior art, the present invention has at least the following beneficial effects: 1. This invention modifies polylactic acid by grafting lysine. Under weakly acidic conditions, carbodiimide reacts with the carboxyl group at the end of polylactic acid to generate an active intermediate. N-hydroxysuccinimide further stabilizes this intermediate, forming a highly reactive N-hydroxysuccinimide ester. The primary amino group of lysine attacks the carbonyl carbon of polylactic acid, undergoing a nucleophilic substitution reaction to form a stable amide bond, which enhances mechanical strength and thus improves the physical strength of the coating.
[0016] 2. In this invention, lysine-grafted modified polylactic acid is intercalated into sodium-based bentonite. The polar groups of the lysine-grafted modified polylactic acid penetrate into the interlayer spaces of the bentonite, widening the gaps between the layers. Simultaneously, strong electrostatic forces overcome the van der Waals forces of the layers, causing some layers to peel off from the stacked state, forming nanosheets uniformly dispersed in the polylactic acid matrix. The bentonite nanosheets act as a rigid reinforcing phase, and the uniformly dispersed layers effectively transfer stress. Furthermore, the parallel arrangement of the nanosheets in the polylactic acid matrix forces corrosive media such as water, oxygen, and chloride ions to bypass them. The polar groups of free lysine can diffuse to the damaged area after corrosion, forming a coordination bond protective film, thereby improving the corrosion resistance of the acrylic dispersion. Attached Figure Description
[0017] The accompanying drawings, which are incorporated herein and form part of the specification, illustrate embodiments of the present disclosure and, together with the specification, further serve to explain the principles of the present disclosure and enable those skilled in the art to implement and use the present disclosure.
[0018] Figure 1 This is a flowchart illustrating a method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings, as used in an embodiment of the present invention. Detailed Implementation
[0019] The following detailed description, in conjunction with the accompanying drawings and specific embodiments, provides an acrylic dispersion suitable for metal anti-corrosion coatings, its preparation, and its application. It should be noted that, to make the embodiments more comprehensive, the following embodiments are the best and preferred embodiments; those skilled in the art can also use other alternative methods to implement some known technologies. Furthermore, the accompanying drawings are only for more specific description of the embodiments and are not intended to specifically limit the invention.
[0020] Example 1: An acrylic dispersion suitable for metal anti-corrosion coatings, its preparation and application, such as Figure 1 As shown, it includes the following steps: S1: Preparation of lysine-grafted modified polylactic acid S1.1: Dissolve 5 parts by mass of polylactic acid in 200 parts by mass of anhydrous dimethyl sulfoxide, stir at 65°C under nitrogen protection until completely dissolved, then cool to 25°C and adjust the pH to 5.5, add 3 parts by mass of EDC and 4 parts by mass of N-hydroxysuccinimide, react for 4 hours to obtain a polylactic acid mixture. S1.2: Add 4 parts by weight of lysine to 100 parts by weight of PBS buffer (pH 8), stir for 5 min to obtain lysine buffer, add polylactic acid mixture to lysine buffer, stir at 25°C for 24 h under nitrogen atmosphere, then pour the reaction solution into ice-cold ether to precipitate, filter to collect solid, wash three times with anhydrous ethanol and deionized water respectively, dialyze with pure water for 48 h, and freeze dry to obtain lysine-grafted modified polylactic acid.
[0021] S2: Preparation of intercalated bentonite composite filler S2.1: Disperse 5 parts by mass of sodium-based bentonite in 500 parts by mass of deionized water, stir at 80°C and 3000 r / min for 10 min, then add 6 parts by mass of octadecyltrimethylammonium chloride, react for 4 h, centrifuge and wash, dry at 60°C for 24 h, pulverize and pass through a 300 mesh sieve to obtain treated bentonite. S2.2: Lysine-grafted modified polylactic acid was dissolved in a chloroform / toluene mixed solvent at a material-to-liquid ratio of 1g:20mL and stirred at 60℃ to obtain a suspension. The chloroform / toluene mixed solvent was prepared by mixing chloroform and toluene at a volume ratio of 4:1. S2.3: Add the treated bentonite to toluene solution at a material-to-liquid ratio of 1g:20mL, and sonicate for 30min at a power of 600W to obtain a bentonite dispersion. S2.4: Add the bentonite dispersion dropwise to the suspension, and simultaneously shear at 5000 r / min for 30 min, heat to 70℃, stir for 6 h to react, and then remove 75% of the solvent by rotary evaporation. Pour the remaining slurry into a polytetrafluoroethylene mold and vacuum dry at 60℃ for 48 h to obtain the intercalated premix. After crushing the intercalated premix, granulate it by extrusion through a twin-screw extruder to obtain the intercalated bentonite composite filler.
[0022] S3: Preparation of acrylic dispersions suitable for metal anti-corrosion coatings 40 parts by mass of methyl methacrylate, 30 parts by mass of butyl acrylate, 5 parts by mass of acrylic acid, and 2 parts by mass of COPS-1 emulsifier were added to 250 parts by mass of deionized water. The mixture was sheared and emulsified at 2000 r / min for 15 min. Under nitrogen protection, the temperature was raised to 80℃, and 0.4 parts by mass of ammonium persulfate aqueous solution was added. The mixture was kept at this temperature for 1 h, cooled to 40℃, and 10 parts by mass of intercalated bentonite composite filler were added. The mixture was stirred at 800 r / min for 10 min. 0.3% of EDC by mass of the total system mass was added, and the mixture was reacted at 40℃ for 2 h to obtain an acrylic dispersion suitable for metal anti-corrosion coatings.
[0023] Example 2: An acrylic dispersion suitable for metal anti-corrosion coatings, its preparation and application, such as Figure 1 As shown, it includes the following steps: S1: Preparation of lysine-grafted modified polylactic acid S1.1: Dissolve 5 parts by mass of polylactic acid in 200 parts by mass of anhydrous dimethyl sulfoxide, stir at 65°C under nitrogen protection until completely dissolved, then cool to 30°C and adjust the pH to 6, add 3 parts by mass of EDC and 4 parts by mass of N-hydroxysuccinimide, react for 4.5 h to obtain a polylactic acid mixture. S1.2: Add 4 parts by weight of lysine to 100 parts by weight of PBS buffer (pH 8), stir for 10 min to obtain lysine buffer, add polylactic acid mixture to lysine buffer, stir at 30°C for 25 h under nitrogen atmosphere, then pour the reaction solution into ice-cold ether to precipitate, filter to collect solid, wash three times with anhydrous ethanol and deionized water respectively, dialyze with pure water for 50 h, and freeze dry to obtain lysine-grafted modified polylactic acid.
[0024] S2: Preparation of intercalated bentonite composite filler S2.1: Disperse 5 parts by mass of sodium-based bentonite in 500 parts by mass of deionized water, stir at 85°C and 3100 r / min for 15 min, then add 6 parts by mass of octadecyltrimethylammonium chloride, react for 4.5 h, centrifuge and wash, dry at 65°C for 25 h, pulverize and pass through a 300 mesh sieve to obtain treated bentonite. S2.2: Lysine-grafted modified polylactic acid was dissolved in a chloroform / toluene mixed solvent at a material-to-liquid ratio of 1g:20mL and stirred at 65℃ to obtain a suspension. The chloroform / toluene mixed solvent was prepared by mixing chloroform and toluene at a volume ratio of 4:1. S2.3: Add the treated bentonite to toluene solution at a material-to-liquid ratio of 1g:20mL, and sonicate for 35min at a power of 600W to obtain a bentonite dispersion. S2.4: Add the bentonite dispersion dropwise to the suspension, and simultaneously shear at 5100 r / min for 35 min, heat to 75℃, and stir for 6.5 h to react. Then, remove 75% of the solvent by rotary evaporation. Pour the remaining slurry into a polytetrafluoroethylene mold and vacuum dry at 65℃ for 50 h to obtain the intercalated premix. After crushing the intercalated premix, granulate it by extrusion through a twin-screw extruder to obtain the intercalated bentonite composite filler.
[0025] S3: Preparation of acrylic dispersions suitable for metal anti-corrosion coatings 40 parts by mass of methyl methacrylate, 30 parts by mass of butyl acrylate, 5 parts by mass of acrylic acid, and 2 parts by mass of COPS-1 emulsifier were added to 250 parts by mass of deionized water. The mixture was sheared and emulsified at 2000 r / min for 15 min. Under nitrogen protection, the temperature was raised to 85℃, and 0.4 parts by mass of ammonium persulfate aqueous solution was added. The mixture was kept at this temperature for 1.5 h, cooled to 45℃, and 10 parts by mass of intercalated bentonite composite filler were added. The mixture was stirred at 850 r / min for 15 min. 0.3% of EDC (by mass of the total system) was added, and the mixture was reacted at 45℃ for 2.5 h to obtain an acrylic dispersion suitable for metal anti-corrosion coatings.
[0026] Example 3: An acrylic dispersion suitable for metal anti-corrosion coatings, its preparation and application, such as Figure 1 As shown, it includes the following steps: S1: Preparation of lysine-grafted modified polylactic acid S1.1: Dissolve 10 parts by mass of polylactic acid in 202 parts by mass of anhydrous dimethyl sulfoxide, stir at 70°C under nitrogen protection until completely dissolved, then cool to 25°C and adjust the pH to 5.5, add 5 parts by mass of EDC and 6 parts by mass of N-hydroxysuccinimide, react for 4 hours to obtain a polylactic acid mixture. S1.2: Add 8 parts by mass of lysine to 105 parts by mass of PBS buffer (pH 8), stir for 5 min to obtain lysine buffer, add polylactic acid mixture to lysine buffer, stir at 25°C for 24 h under nitrogen atmosphere, then pour the reaction solution into ice-cold ether to precipitate, filter to collect solid, wash three times with anhydrous ethanol and deionized water respectively, dialyze with pure water for 48 h, and freeze dry to obtain lysine-grafted modified polylactic acid.
[0027] S2: Preparation of intercalated bentonite composite filler S2.1: Disperse 8 parts by mass of sodium-based bentonite in 510 parts by mass of deionized water, stir at 3000 r / min for 10 min at 80℃, then add 7 parts by mass of octadecyltrimethylammonium chloride, react for 4 h, centrifuge and wash, dry at 60℃ for 24 h, pulverize and pass through a 300 mesh sieve to obtain treated bentonite. S2.2: Lysine-grafted modified polylactic acid was dissolved in a chloroform / toluene mixed solvent at a material-to-liquid ratio of 1g:22mL and stirred at 60℃ to obtain a suspension. The chloroform / toluene mixed solvent was prepared by mixing chloroform and toluene at a volume ratio of 5:1. S2.3: Add the treated bentonite to toluene solution at a material-to-liquid ratio of 1g:22mL, and sonicate for 30min at a power of 600W to obtain a bentonite dispersion. S2.4: Add the bentonite dispersion dropwise to the suspension, and simultaneously shear at 5000 r / min for 30 min, heat to 70℃, stir for 6 h to react, and then remove 75% of the solvent by rotary evaporation. Pour the remaining slurry into a polytetrafluoroethylene mold and vacuum dry at 65℃ for 50 h to obtain the intercalated premix. After crushing the intercalated premix, granulate it by extrusion through a twin-screw extruder to obtain the intercalated bentonite composite filler.
[0028] S3: Preparation of acrylic dispersions suitable for metal anti-corrosion coatings 45 parts by weight of methyl methacrylate, 35 parts by weight of butyl acrylate, 8 parts by weight of acrylic acid, and 2.5 parts by weight of COPS-1 emulsifier were added to 260 parts by weight of deionized water. The mixture was sheared and emulsified at 2000 r / min for 15 min. Under nitrogen protection, the temperature was raised to 80℃, and 0.5 parts by weight of ammonium persulfate aqueous solution was added. The mixture was kept at this temperature for 1 h, cooled to 40℃, and 15 parts by weight of intercalated bentonite composite filler were added. The mixture was stirred at 800 r / min for 10 min. 0.5% of EDC by weight of the total mass of the system was added, and the mixture was reacted at 40℃ for 2 h to obtain an acrylic dispersion suitable for metal anti-corrosion coatings.
[0029] Comparative Example 1: Compared with Example 1, the difference of Comparative Example 1 is that polylactic acid mixture is not added in step S1.2, while the other steps remain the same. The prepared acrylic dispersion is referred to as Comparative Example 1.
[0030] Comparative Example 2: Compared with Example 1, Comparative Example 2 differs in that lysine buffer is not added in step S1.2, while the other steps remain unchanged. The prepared acrylic dispersion is referred to as Comparative Example 2.
[0031] Comparative Example 3: Compared with Example 1, the difference of Comparative Example 3 is that bentonite dispersion is not added in step S2.4, while the other steps remain the same. The prepared acrylic dispersion is referred to as Comparative Example 3.
[0032] Comparative Example 4: Comparative Example 4 is a commercially available acrylic dispersion suitable for metal anti-corrosion coatings, specifically the DA766 water-resistant and corrosion-resistant modified acrylic dispersion sold by Shanghai Juling Chemical Technology Co., Ltd.
[0033] The acrylic dispersions prepared in Examples 1-3 and Comparative Examples 1-4 were mixed, dispersed, ground, and stirred with acrylic dispersant, defoamer, and rheology modifier in a volume ratio of 85:1:2. The mixture was then coated onto a carbon steel plate with a thickness of 1 mm. The corrosion resistance was tested using the method in GB / T1771-2007 "Determination of resistance to neutral salt spray in paints and varnishes", as shown in Table 1. The pencil hardness, i.e. physical hardness, was tested using the method in GB / T6739-2022 "Determination of Hardness of Paints and Varnishes by Pencil Method", as shown in Table 2. The solid content, viscosity, particle size distribution, acid value, and degree of neutralization of the acrylic dispersions obtained in Test Examples 1-3 are shown in Table 3.
[0034] Table 1 Typical salt spray tolerance time (h) Performance Example 1 240 No blistering, no rust Example 2 240 No blistering, no rust Example 3 240 No blistering, no rust Comparative Example 1 200 Slight bubbling, no rust in the unmarked area. Comparative Example 2 190 Slight bubbling, no rust in the unmarked area. Comparative Example 3 170 Slight bubbling, no rust in the unmarked area. Comparative Example 4 200 No blistering, no rust Table 2 Pencil hardness Example 1 2H Example 2 2H Example 3 2H Comparative Example 1 HB Comparative Example 2 HB Comparative Example 3 HB Comparative Example 4 HB Table 3 Solid content viscosity Particle size distribution acid value Neutralization Example 1 45% 328 mPa·s 100-300nm 38mgKOH / g 82% Example 2 47% 329 mPa·s 100-300nm 38mgKOH / g 81% Example 3 46% 328 mPa·s 100-300nm 38mgKOH / g 82% As can be seen from Table 1, Examples 1-3, containing polylactic acid, lysine buffer, and suspension, all achieved a salt spray resistance time of 240 hours without bubbling or rust, demonstrating the best anti-corrosion performance. Comparative Example 1, lacking polylactic acid, Comparative Example 2, lacking lysine buffer, and Comparative Example 3, without bentonite dispersion, showed reduced salt spray resistance time and inferior performance compared to the Examples. Comparative Example 4, a commercially available product, had a salt spray resistance time of 200 hours, comparable to Comparative Example 1, but without bubbling. This indicates that Examples 1-3 of the present invention are superior to commercially available products in terms of anti-corrosion performance and have practical application advantages.
[0035] As can be seen from Table 2, the pencils of Examples 1-3 have a hardness of 2H, which is significantly higher than that of all comparative examples.
[0036] The hardness of Comparative Examples 1-3 was HB, which was much lower than that of the Example, indicating that the synergistic effect of the two components, polylactic acid and lysine, and the influence of lysine grafted and modified polylactic acid intercalation into bentonite on the coating hardness. The hardness of the commercially available product in Comparative Example 4 was HB, which was the same as that of Comparative Examples 1-3, further proving that the present invention has a significant advantage in hardness.
[0037] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings, characterized in that, Includes the following steps: S1: Preparation of lysine-grafted modified polylactic acid Polylactic acid was dissolved in anhydrous dimethyl sulfoxide, and EDC and N-hydroxysuccinimide were added. The mixture was reacted to obtain a polylactic acid mixture. Lysine was added to PBS buffer and stirred to obtain a lysine buffer. The polylactic acid mixture was added to the lysine buffer and stirred. The reaction solution was then poured into ice-cold ether to precipitate. The solid was collected by filtration, dialyzed with pure water, and freeze-dried to obtain lysine-grafted modified polylactic acid. S2: Preparation of intercalated bentonite composite filler Sodium-based bentonite was dispersed in deionized water and stirred. Octadecyltrimethylammonium chloride was then added to react and obtain treated bentonite. Lysine-grafted modified polylactic acid was dissolved in a chloroform / toluene mixed solvent and stirred to obtain a suspension. The treated bentonite was added to a toluene solution and ultrasonically treated to obtain a bentonite dispersion. The bentonite dispersion was added dropwise to the suspension, and the mixture was sheared at high speed, stirred, and dried to obtain an intercalated premix. The intercalated premix was pulverized and extruded to granulate to obtain an intercalated bentonite composite filler. S3: Preparation of acrylic dispersions suitable for metal anti-corrosion coatings Methyl methacrylate, butyl acrylate, acrylic acid, and emulsifier were added to deionized water and sheared and emulsified. Ammonium persulfate aqueous solution was added, and the reaction was carried out under heat. Intercalated bentonite composite filler was added, and the mixture was stirred. EDC was added, and the reaction was carried out to obtain an acrylic dispersion suitable for metal anti-corrosion coatings.
2. The method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to claim 1, characterized in that, Step S1 prepares lysine-grafted modified polylactic acid, including the following steps: S1.1: Dissolve 5-10 parts by weight of polylactic acid in 200-202 parts by weight of anhydrous dimethyl sulfoxide, stir at 65-70°C under nitrogen protection until completely dissolved, then cool to 25-30°C and adjust the pH to 5.5-6, add 3-5 parts by weight of EDC and 4-6 parts by weight of N-hydroxysuccinimide, react for 4-4.5 h to obtain a polylactic acid mixture; S1.2: Add 4-8 parts by weight of lysine to 100-105 parts by weight of PBS buffer and stir for 5-10 min to obtain lysine buffer. Add polylactic acid mixture to lysine buffer and stir at 25-30℃ for 24-25 h under nitrogen atmosphere. Then pour the reaction solution into ice-cold ether to precipitate, filter to collect solid, wash three times with anhydrous ethanol and deionized water respectively, dialyze with pure water for 48-50 h, and freeze-dry to obtain lysine-grafted modified polylactic acid.
3. The method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to claim 2, characterized in that, Step S2, preparing the intercalated bentonite composite filler, includes the following steps: S2.1: Disperse 5-8 parts by weight of sodium-based bentonite in 500-510 parts by weight of deionized water, stir at 80-85℃ and 3000-3100 r / min for 10-15 min, then add 6-7 parts by weight of octadecyltrimethylammonium chloride, react for 4-4.5 h, centrifuge and wash, dry at 60-65℃ for 24-25 h, pulverize and pass through a 300 mesh sieve to obtain treated bentonite; S2.2: Lysine-grafted modified polylactic acid was dissolved in a chloroform / toluene mixed solvent at a material-to-liquid ratio of 1g:(20-22)mL and stirred at 60-65℃ to obtain a suspension; S2.3: Add the treated bentonite to toluene solution at a material-to-liquid ratio of 1g:(20-22)mL, and sonicate for 30-35min to obtain a bentonite dispersion; S2.4: Add the bentonite dispersion dropwise to the suspension, and simultaneously shear at 5000-5100 r / min for 30-35 min, heat to 70-75℃, and stir for 6-6.5 h to react. Then, remove 75-80% of the solvent by rotary evaporation. Pour the remaining slurry into a polytetrafluoroethylene mold and vacuum dry at 60-65℃ for 48-50 h to obtain the intercalated premix. After crushing the intercalated premix, granulate it by extrusion through a twin-screw extruder to obtain the intercalated bentonite composite filler.
4. The method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to claim 3, characterized in that, Step S3, preparing an acrylic dispersion suitable for metal anti-corrosion coatings, includes the following steps: Add 40-45 parts by weight of methyl methacrylate, 30-35 parts by weight of butyl acrylate, 5-8 parts by weight of acrylic acid, and 2-2.5 parts by weight of emulsifier to 250-260 parts by weight of deionized water, and shear emulsify at 2000-2100 r / min for 15-20 min. Under nitrogen protection, heat to 80-85℃, add 0.4-0.5 parts by weight of ammonium persulfate aqueous solution, keep the reaction at this temperature for 1-1.5 h, cool to 40-45℃, add 10-15 parts by weight of intercalated bentonite composite filler, stir at 800-850 r / min for 10-15 min, add 0.3-0.5% by weight of EDC (ethyl acetate) of the total system mass, and react at 40-45℃ for 2-2.5 h to obtain an acrylic dispersion suitable for metal anti-corrosion coatings.
5. The method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to claim 2, characterized in that, The pH of the PBS buffer is 8-8.
5.
6. The method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to claim 3, characterized in that, The chloroform / toluene mixed solvent is prepared by mixing chloroform and toluene in a volume ratio of (4-5):
1.
7. The method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to claim 3, characterized in that, The power of the ultrasonic treatment is 600W.
8. The method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to claim 4, characterized in that, The emulsifier is COPS-1 emulsifier.
9. An acrylic dispersion suitable for metal anti-corrosion coatings, characterized in that, It is prepared by the method for preparing an acrylic dispersion suitable for metal anti-corrosion coatings according to any one of claims 1-8.
10. The application of an acrylic dispersion according to claim 9 for use in metal anti-corrosion coatings, characterized in that, It is used in the preparation of metal anti-corrosion coatings.
